PENERAPAN MODEL PEMBELAJARAN DISCOVERY LEARNING UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN KOLOID DI KELAS XI IPA SMA NEGERI 2 TAMBANG - Fitrida Boang Manalu; Betty Holiwarni; Herdini ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract:The research aims to improve student learning achievementon the topic of colloid in XI science class of SMAN 2 Tambang by implementation of discovery learning model. The research is a kind of experiment research with pretest-posttest design. The sample consists of two classes, class XI science 3 as an experimental class and class XI science 4 as the control class is determined randomly after normality test and homogeneity test. Experimental class is a class that is applied of discovery learning while the control class was not. Data analysis technique used is the t-test. Based on data analysis of data obtained tcount>ttable is 3,52> 1,66 means that the implementation of discovery learning model can improve student learning achievement on the topic of colloid in XI science class of SMAN 2 Tambang. The result show that the average n-gain ternormalisasi in control class was 0,58 and eksperiment class was 0,75.